The Effectiveness of NEM (Nutrizone Educational Media) Compared with Knowledge and Attitudes in Early Adults in The West Jakarta Region - Laras Sitoayu; Daniel Hartanto; Lintang Purwara Dewanti; Harna Harna; Mertien Sa'pang (Faculty of Public Health Universitas Indonesia, 2023)
AbstractMetabolic syndrome is a disease that often occurs in early adulthood. Maintaining a good lifestyle to prevent non-communicable diseases is very important to maintain a good quality of life. In early adulthood, most of them are still not exposed to information related to metabolic syndrome, so it is necessary to provide interventions associated with it. This study uses the Nutrizone gameboard intervention media. Good early adults’ knowledge and attitude about Metabolic Syndrome may lead to a good lifestyle that prevents them from suffering from NCDs. An intervention media may improve their knowledge and attitude. The research design used was pre-experimental one with subjects of 40 early adults. They received one-time education using Nutrizone Media and showed Significance difference scores before and after intervention based on paired sample t-test and Wilcoxon test. Nutrizone board games can improve early adult knowledge and attitudes to be used as educational media. Keywords: Nutrizone, knowledge of metabolic syndrome, attitude toward metabolic syndrome AbstrakSindrom metabolik adalah suatu penyakit yang sering terjadi dikalangan dewasa awal. Menjaga gaya hidup yang baik untuk mencegah penyakit tidak menular terjadi sangatlah penting untuk menjaga kualitas hidup yang baik. Pada masa dewasa awal juga Sebagian besar masih kurang terpapar informasi terkait sindrom metabolik sehingga perlu diberikan intervensi terkait sindrom metabolik. Penelitian ini menggunakan media intervensi permainan papan (gameboard) nutrizone. Penelitian ini bertujuan untuk mengetahui pengaruh nutrizone terhadap pengetahuan dan sikap dewasa awal terhadap sindrom metabolik. Metode penelitian yang digunakan adalah Quasi Experimental Pre dan Post-test design dan jumlah responden sebanyak 40 orang dewasa awal. Responden mendapat edukasi menggunakan media nutrizone, berdasarkan uji Paired Sample T-test, dan Wilcoxon didapatkan hasil ada perbedaan pengetahuan serta sikap sindrom metabolik (p<0.05). Permainan papan nutrizone dapat meningkatkan pengetahuan dan sikap dewasa awal sehingga dapat digunakan sebagai media edukasi. Kata kunci: Nutrizone, pengetahuan sindrom metabolik, sikap sindrom metabolik